Aplikasi Praktis Metode Pengembangan Cepat (RAD) Dalam Sistem Manajemen Penjualan Dan Pengembalian Barang Berbasis Web - Annisa, Riski; Meilinda, Eva; Yustisio, Sendi (Jurnal Informatika Kaputama (JIK), 2024)
In the process of recording sales transactions at Toko Kurnia Jaya always use a manual typewriter so that it is not effective and inaccurate in recording sales transactions, and sales notes are still manual on paper. Another problem is in the process of returning goods, if the goods purchased by the buyer are not appropriate. From these problems, it is formulated how to build a web-based application for recording sales transactions and returning goods. The data collection method that the author uses in completing this report is the method of observation, interviews and library studies. The system development model that the author uses is the RAD model, the programming language that the author uses is PHP and MySql as a database and tested using the Blackbox testing method. With the application of processing sales transactions and returning goods, it can facilitate the search for goods data and more quickly find information about the price of goods and make it easier to manage transaction data, both knowing the total sales results, returning goods and recording incoming goods data.